Nocturnal blood pressure alterations in patients with preeclampsia – Do they really matter? A systematic review of the literature. (August 2019) - Pergialiotis, Vasilios; Karampetsou, Nikoleta; Bellos, Ioannis; Papantoniou, Nikolaos; Daskalakis, Georgios
Abstract: The significance of blood pressure alterations during night-time has been already recorded in essential hypertension and several studies have been conducted to guide current clinical practice. To date, however, there is no consensus regarding the need for screening patients with preeclampsia for nocturnal hypertension as evidence in this field remain scarce. The purpose of this study is to accumulate current data in this field and serve as a pilot for the conduct of future studies. The present systematic review was designed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. We used the Medline, Scopus, Clinicaltrials.gov, EMBASE, Cochrane Central Register of Controlled Trials CENTRAL and Google Scholar databases in our primary search along with the reference lists of electronically retrieved full-text papers. Overall, six studies were included in our systematic review that recruited 487 pregnant women. Their methodological quality was evaluated as average according to the Newcastle-Ottawa criteria. The majority of those studies pointed towards significant differences in nocturnal blood pressure patterns among patients with preeclampsia and controls. However, its clinical value in determining pregnancy outcomes remains unknown as only one small case control study investigated outcomes of patients with severe preeclampsia and different patterns of nocturnal blood pressure and reported that differences were non-significant. Concluding, current evidence supports that nocturnal hypertension seems to be more prevalent in cases complicated by preeclampsia; however, its clinical usefulness in determining pregnancy outcomes remains, to date, unknown.